Analysis of strengthening the traditional system of village head elections viewed from the democratic aspect - Imran, Abdul Muammar; Hayat, Hayat; Andza, Hirzhi (LEGAL BRIEF, 2024)
This research tries to look again at the government system through the Lamahala Adonara Custom of East Flores. This shows that even though Lamahala Jaya is covered by binding customary rules, traditional stakeholders and the community still respect the implementation of democracy in Indonesia. Lamahala Jaya as one of the traditional villages in Indonesia has become a tradition passed down from generation to generation that in carrying out the wheels of power so that they continue to follow the inherited customary system. The aim of this research is to find out the common ground that occurs in the implementation of democracy adopted by Indonesia based on the rules of the Constitution and the rules of the customary system that applies in Lamahala Jaya Village. This research uses a qualitative approach because it can directly create a more sensitive relationship between researchers and informants. The process of selecting the Village Head in Lamahala Jaya Village, East Adonara District, East Flores Regency began with the formation of a committee by the Bela Tribe of Telo whose members came from Kapitan Pulo and Pegawe Lema, followed by the election of the Village Head with the criteria of being devoted to God Almighty, knowing history, coming from from the Bela Telo tribe, wise, fair, honest and humane